Prespektif orang tua dan guru dalam perkembangan karakter profil pelajar Pancasila: SD Muhammadiyah 1 GKB - Mochammad Nor Qomari; Siti Maghfirotun Nikmah (Universitas Muhammadiyah Gresik, 2023)
This study aims to determine the character development of students in the dimensions of the Pancasila student profile as a form of evaluation in the framework of following up the independence curriculum that has been implemented at SD Muhammadiyah 1 GKB in the 2021/2022 academic year. This research is a qualitative descriptive study. The data collection method used in this study was a survey, while the data collection technique used an instrument in the form of a questionnaire. The data was analyzed using the percentage of questionnaire data as an evaluation in the framework of following up the independence curriculum that had been implemented at SD Muhammadiyah 1 GKB. The results of this analysis show changes in IKM education services, project learning and implementation of Pancasila student profile strengthening projects, namely: faith, piety to God Almighty and noble character, global diversity, mutual cooperation, independent critical reasoning, and creative filled by people parents and teachers show that the implementation of the independent curriculum at SD Muhammadiyah 1 GKB is in very good criteria.